MANAGEMENT OF LEARNING FACILITIES TO SUPPORT THE QUALITY OF EDUCATION AT STATE VOCATIONAL HIGH SCHOOL OF AGRICULTURE DEVELOPMENT JAMBI - SOLIHIN; Muazza; KA. Rahman; Hestiwidayani (International Jurnal of Education Schoolars, 2020)
The State Vocational High School of Agriculture for Development of Jambi is one of the vocational schools that educates students to become skilled personnel in agriculture and is quite famous for its achievements. One of the success factors is the completeness of learning facilities. Learning facilities are an important factor in supporting the quality of education. There are schools that have complete facilities but are still not optimally managed so that they cannot be used optimally. Therefore, an effective and efficient management of learning facilities is needed to overcome this. This study aims to describe the management of learning facilities, constraints and solutions in managing learning facilities to support the quality of education at SMK N PP Jambi. The research conducted is descriptive qualitative. The informants in this study were the deputy head of the learning facility, the head of the laboratory, the head of the workshop, the head of the library, the teacher and the students. In determining the informants using purposive sampling technique based on information from the dapodic operator of SMKN PP Jambi. Data obtained through the method of observation, interviews, and documentation. The validity of the data used the triangulation method with the type of source triangulation and method triangulation. Furthermore, the data were analyzed using interactive analysis from Milles and Hubberman, which consisted of: data collection, data reduction, and conclusion / verification. The results of this study indicate that: (1) Management of learning facilities at the Jambi Development Agricultural State Vocational High School includes planning, procurement, regulation, use, and elimination. The steps in planning include needs analysis, cost estimation, prioritization and preparation of a procurement plan. The source of funds is obtained from the School Operational Assistance, assistance from the Human Resources Development Agency of the Ministry of Agriculture and alumni assistance. Regulatory activities include inventory, storage and maintenance. The use of learning facilities has set a schedule that has been prepared to avoid clashes in usage. The removal process is carried out to avoid the accumulation of goods that cannot be used. (2) The constraints faced, among others, relate to the cost and low awareness of teachers or students to maintain existing learning facilities.